1981
DOI: 10.1071/mf9810967
|View full text |Cite
|
Sign up to set email alerts
|

Diet and growth of rainbow trout, Salmo gairdneri Richardson, in two streams on the New England Tableland, New South Wales

Abstract: The diets and growth rates of rainbow trout in the Wollomombi and Guy Fawkes Rivers in northern New South Wales were examined. The growth rate of trout in the Wollomombi River was much higher than that of fish in the Guy Fawkes River. Spearman rank correlation coefficients indicated that stream type was more important than fish size in determining the composition of the diet of the trout. Benthic invertebrates formed the largest component of the diet in both streams: 66.0 and 63.0% of ash-free dry weight (AFDW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This finding is similar to a study by Pidgeon (1981) in two streams in New South Wales that demonstrated that freshwater crayfish increase in proportions in the diets of larger O. mykiss. The dominance of C. cainii in O. mykiss diets in Churchman Brook Reservoir suggests that O. mykiss is a specialist and/or opportunistic predator in this system; selecting the most accessible prey and larger prey that provide a large proportion of total energy intake (Tilzey 1977).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is similar to a study by Pidgeon (1981) in two streams in New South Wales that demonstrated that freshwater crayfish increase in proportions in the diets of larger O. mykiss. The dominance of C. cainii in O. mykiss diets in Churchman Brook Reservoir suggests that O. mykiss is a specialist and/or opportunistic predator in this system; selecting the most accessible prey and larger prey that provide a large proportion of total energy intake (Tilzey 1977).…”
Section: Discussionsupporting
confidence: 92%
“…The considerable predatory impact of introduced rainbow trout (Oncorhynchus mykiss Walbaum 1792) on native aquatic fauna is widely acknowledged (Jenkins 1952;Tilzey 1976;Pidgeon 1981;Cadwallader & Eden 1982;Welcomme 1984;Crowl et al 1992;Fuller et al 1999), resulting in this species being included by the IUCN in the list of 100 of the world's worst invasive alien species (Lowe et al 2000;Lintermans 2004). Rainbow trout were first introduced into waters of southwest Western Australia in 1902 and large-scale stocking of the species began in the 1930s (Coy 1979), with c. 2.5 million O. mykiss stocked into public waterways for recreational fishing between 1999 and 2004 (Astbury 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Alien trout species are known to predate on juveniles of Euastacus species (Sydney Morning Herald (SMH) 1937;Pigeon 1981;Horwitz 1990Horwitz , 1995Furse and Coughran 2011a;McCormack 2012) and alien trout predation is noted as a specific conservation concern for the Orbost spiny cray (Euastacus diversus) (Murray 2003;Lieschke et al 2014), the alpine cray (Euastacus crassus) (van Praagh 2003) and the West Australian marron (Cherax cainii) (Tay et al 2007). The impact of alien fish predation on juvenile Euastacus, particularly predation by alien trout species, has scarcely been researched and is in need of urgent investigation and quantification.…”
Section: Low Numbers Of Observed Crayfish In the Lower Goodradigbee R...mentioning
confidence: 99%